2006
DOI: 10.1080/02699200400027031
|View full text |Cite
|
Sign up to set email alerts
|

Speech perception of children with cochlear implants and children with traditional hearing aids

Abstract: The aim of the study was to analyse speech perception of children with cochlear implants (N = 29) and children fitted with traditional hearing aids (N = 20). One- and two-syllable words were presented auditorily in a forced choice minimal-pair discrimination task. The children repeated the word and pointed to the appropriate picture presented on computer screen. The words were minimal pairs with respect to voicing or place of articulation in stops and fricatives; among affricates the minimal pairs included the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 19 publications
2
17
0
4
Order By: Relevance
“…Additionally, Geers (2003) reported that a considerable amount of the variance in reading scores of children who use CIs could be accounted for by child and family variables as well as speech and language variables. Studies also find that the CI provides better access to speech for most children, and this access results in improved speech perception and production (Mildner, et al, 2006;Peng, et al, 2004;Tobey, et al, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…Additionally, Geers (2003) reported that a considerable amount of the variance in reading scores of children who use CIs could be accounted for by child and family variables as well as speech and language variables. Studies also find that the CI provides better access to speech for most children, and this access results in improved speech perception and production (Mildner, et al, 2006;Peng, et al, 2004;Tobey, et al, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…Speech sound production skills were assessed with the GoldmanFristoe Test of Articulation-2 (GFTA-2; Goldman & Fristoe, 2000). Speech sound production errors involving sounds differing by one phonetic feature (e.g., /d/ vs. /g/) are common in children with hearing loss and could potentially lead researchers to incorrectly interpret verbal responses (Mildner, Sindija, & Zrinski, 2006). Therefore, this testing was completed so researchers could be confident that the verbal responses provided by both groups of children were being accurately decoded by examiners.…”
Section: Speech and Language Measuresmentioning
confidence: 99%
“…Support for this assumption can be found in studies of children with CIs, which tend to find that speech perception improves more with earlier implantation (Blamey, Sarant, Paatsch, Barry, Bow, Wales, Wright, Psarros, Rattigan, and Tooher, 2001b;Wu and Yang, 2003;Mildner, Šindija, and Zerinski, 2006). In a study of Mandarin-speaking hearing-impaired children, Wu and Yang (2003) concluded that speech perception improved over a 2-year follow-up period, with improvements negatively correlated with the age at implantation and positively correlated with the duration of implant use.…”
Section: Speech Production and Perceptionmentioning
confidence: 75%